Systematic Literature Review of Corporate Sustainability and Financial Performance Linkages - Veera Suchitra; Bietsch Samantha; Jones Susan; Ward Paul (Organizacijų Vadyba: Sisteminiai Tyrimai)
This study analyzes the linkages between corporate sustainability and financial performance of companies by conducting a systematic review of prior literature. The findings provide insights on the relationship between sustainable practices and companies’ financial outcomes.